A Modified Open Loop Control of a Matrix Converter Connected to Wind Energy System - Kotb Tawfiq; A.F. Abdou; E. E. EL-Kholy; S. S. Shokralla (Renewable Energy and Sustainable Development, 2017)
Wind energy conversion system (WECS) is bit by bit gaining interest as a suitable source of renewable energy. In this paper a direct AC-AC matrix converter is utilized to interface an isolated static load fed from WECS. A self-excited induction generator is utilized as it has many advantages in terms of ease of maintenance, self-protection against short circuits. This paper proposes a modified open loop control of matrix converter with indirect space vector modulation. The modified open loop provides constant output voltage and constant frequency even if the wind speed changed. Matrix converter (MC) is used rather than AC-DC-AC converter as it eliminates the bulky capacitors. Finally, simulation results for different operating points are displayed which are consistent with the expected results.